A ilusão do Pampa : uma leitura de Délibàb, de Vitor Ramil - Moraes, Marcos Ferreira de (2013)
The work Délibàb, released in 2010 by the composer and musician Vitor Ramil, expresses the lyricism of the Argentine writer Jorge Luis Borges and of the Brazilian poet João da Cunha Vargas, performing a fusion of languages music and poetry that reveals a chance to get closer, through art, the knowledge that is called classical and the popular. The album incorporates historical aspects of Southern Latin America and tells, by means of the milonga, dilemmas such as love, loneliness, death and the customs that make up the identity of the gaucho who lives in pampa . To verify the relationship intertextual and dialogic, present in songs by Délibàb, this work is structured, initially, in a literature search that conceptualized the human language by the essence of the creator word, as the theoretical assumptions of Walter Benjamim, and presents the man as a semiotician, in Russian linguist Mikhail Bakhtin s understanding. As a result, it is a relationship that seeks to clarify the manifestation of language through poetry and music, delimiting some historical and literary peculiarities related to the pampa rio-grandense . Assuming an analytical approach about the songs Deixando o Pago and Milonga de Albernoz, intending to reveal specific points that identify the artistic language as a means to put the different forms of knowledge in dialogue, the goal is to avoid an evaluative classification that hierarchical knowledge, prioritizing the key contents that provide clues to an understanding more harmonic about the man in relation to culture